2011
DOI: 10.1038/ajg.2011.11
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Adherence to Fecal Occult Blood Testing Impacts Colorectal Cancer Screening Quality

Abstract: Adherence to repeated FOBT is low, suggesting that cross-sectional measurements of quality may overestimate the programmatic success of CRC screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 25 publications
1
64
1
Order By: Relevance
“…Other studies have evaluated longitudinal adherence to other, non-CC screening programmes over time (18)(19)(20), but did not consider multiple levels of underscreening, over-screening, nor the ability to differentiate cancer outcomes. We found that longitudinal adherence was lower than cross-sectional adherence within the last screening round; similar results were found for cervical, colorectal, and breast cancer screening elsewhere (17,21,22), suggesting that attendance over multiple screening rounds more accurately reflects screening performance.…”
Section: Discussionsupporting
confidence: 61%
“…Other studies have evaluated longitudinal adherence to other, non-CC screening programmes over time (18)(19)(20), but did not consider multiple levels of underscreening, over-screening, nor the ability to differentiate cancer outcomes. We found that longitudinal adherence was lower than cross-sectional adherence within the last screening round; similar results were found for cervical, colorectal, and breast cancer screening elsewhere (17,21,22), suggesting that attendance over multiple screening rounds more accurately reflects screening performance.…”
Section: Discussionsupporting
confidence: 61%
“…This may occur when there is no or a suboptimal invitation system, as it is often the case in countries with a decentralised health system. For example, a retrospective cohort analysis from the USA evaluating adherence to repeated yearly FOBT showed that among 395 000 subjects who received exclusively FOBT and no other screening tool, about 40% were tested only once during a 5-year study period 15. If strategies with a longer screening interval are used, the design needs to make sure that non-participants are reinvited after a reasonable time frame and not several years later when invitation to the next screening round is due.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of trials to evaluate the efficacy of CRCS have reported rates of repeat screening (Hardcastle et al, 1986, 1989, 1996; Mandel et al, 1999), very few studies have examined psychosocial predictors of regular screening. Studies of repeat FOBT conducted in community settings report completion rates between 14 and 54% among persons who had previously completed an FOBT on schedule (Fenton et al, 2010; Gellad et al, 2011; Liss et al, 2013; Myers et al, 1993). Receipt of a prior preventive health examination, younger age, lesser comorbidity, and a greater number of physician visits were significantly associated with repeat CRCS (Fenton et al, 2010; Liss et al, 2013; Myers et al, 1993).…”
Section: Introductionmentioning
confidence: 99%